1985
DOI: 10.1007/bf00389451
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomes of human sperm: Variability among normal individuals

Abstract: The chromosomal constitution of 2468 human sperm cells has been investigated by fusion of human sperm with hamster eggs. The overall frequency of cells with structural aberrations was 7.7%, ranging from 1.9% to 15.8%, and varying significantly among individuals. The highest frequency occurred in sperm from the oldest donor (49 years), who also had had a vasectomy reversal three years prior to sampling. The overall aneuploidy frequency was 1.7%, ranging from 0.6% to 3.1%. In nine out of ten donors from whom blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
58
3
4

Year Published

1987
1987
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(70 citation statements)
references
References 21 publications
5
58
3
4
Order By: Relevance
“…Using this datum, mean frequencies of XX-and YY-sperm in this study are calculated to be 0.18% and 0.15%, respectively. The disomy rates for autosomes in this study are generally higher than those estimated from conventional cytogenetic studies on hamster eggs (Martin, 1985;Brandriff et al, 1985). The discrepancies of the disomy rates between FISH and karyotype studies may be due to the limited number of total sperm in the karyotype studies.…”
Section: Discussioncontrasting
confidence: 68%
“…Using this datum, mean frequencies of XX-and YY-sperm in this study are calculated to be 0.18% and 0.15%, respectively. The disomy rates for autosomes in this study are generally higher than those estimated from conventional cytogenetic studies on hamster eggs (Martin, 1985;Brandriff et al, 1985). The discrepancies of the disomy rates between FISH and karyotype studies may be due to the limited number of total sperm in the karyotype studies.…”
Section: Discussioncontrasting
confidence: 68%
“…In addition, it is known that injury to sperm DNA after second meiosis is not repaired, and that DNA-fragmented sperm are found in human ejaculate. Although the ratios of abnormal sperm in humans and in experimental animals were reported to be 9.3-15.5% [3,20] and 0.9-1.4% [9], respectively, and that of DNA-fragmented sperm in human ejaculate was reported to be 20-70% [13], the ratios of DNA-fragmented sperm in wild animals or in endangered animals may be higher than in humans or experimental animals. As the number of DNA-fragmented sperm increases, the fertilization rate of the sperm is thought to rise, so DNA fragmentation of sperm might affect embryo development.…”
Section: Discussionmentioning
confidence: 99%
“…The excess of duplications observed in sperm nuclei could be a reflection of the excess in acentric fragments described in sperm karyotypes. 15,[18][19][20][21] and metaphase I spermatocytes. 31 Acentric fragments can either acquire a neocentromere and be rescued, or be lost.…”
Section: Discussionmentioning
confidence: 99%
“…Other authors noticed a trend toward elevated frequencies of breaks and/or acentric fragments with age but without reaching statistical significance. 15,20,21 There have been further reports using multicolor FISH in decondensed human sperm heads but each study has been limited to a particular chromosome. Using this approach, a positive age effect on the frequencies of duplications and deletions for the centromeric and subtelomeric regions of chromosome 9 was reported by Bosch et al 22 and, similarly, Sloter et al 23 found that sperm of older men carried more breaks and segmental duplications and deletions of chromosome 1.…”
Section: Introductionmentioning
confidence: 99%